Contact-Intensity, Collapsing Entertainment Sector and Wage Inequality: A Finite Change Model of Covid-19 Impact - Sugata Marjit; Gouranga Gopal Das (Center for Economic Studies and ifo Institute (CESifo), 2021)
In a general equilibrium model with online, entertainment and informal sectors employing skill, unskilled, and capital, we show that Covid-19 could cause polarization pushing contact-intensive entertainment industry on the brink of collapse while other two survive. Dual roles of factor-intensity and contact-intensity contribute to such finite changes, triggering inter-skill wage inequality.
Keywords: D50; I18; J31; L80; N30; O10; 330; wage-gap; Covid; contact-intensive; general equilibrium